Abstimmung der Entwicklungsplanung in Stadtregionen. Der Stellenwert von Leitbildern und interkommunaler Kooperation in der Region München. - Haberer, Thomas; Mailer, Markus (Deutscher Verkehrs-Verlag, 2005)
Die Probleme und Lösungsperspektiven zu Fragen der Siedlungs- und Verkehrsentwicklung haben längst die Grenzen einzelner Kommunen überschritten. Daher stellt sich vor allem in Stadtregionen immer stärker die Frage, inwieweit Städte und Gemeinden bereit sind, diesen Herausforderungen durch kooperative Entwicklungsstrategien zu begegnen. difu

In recent decades, growing urban settlements and traffic volume have created special challenges for the so-called "dynamic metropolitan areas", which can only partially be dealt with by using recognized methods and instruments in the planning process. In Germany, numerous local authorities have, therefore, opted for voluntary and informal ways of solving problems related to this subject matter, also in cross border cases. In the metropolitan area of Munich, investigations have been carried out exemplarily about the role and contribution of such base factors as "Leitbilder" (models) and intercommunal cooperation. It is noted that, during the investigations, such factors have only rarely been made use of. Differences exist between the "Leitbilder" and concepts of future development with regard to the stages in planning already completed and thus in their significance for the planning process as a whole. Insufficient coordination among local authorities and the various levels of administration may cause conflict over time-related factors. Coordinated development planning for the metropolitan area of Munich can, therefore, only be achieved if adjustments are made to the entire planning process. difu
Keywords: Verkehr; Verkehrsentwicklung; Verkehrsplanung; Stadtregion; Leitbild; Kommunale Zusammenarbeit; Verkehrsmodell; Regionalentwicklung